Kānprayuk chai rabop sārasonthēt phūmisāt phư̄a kānwikhro̜ læ wāngphǣn čhatkān phư̄nthī sīang phai din thalom / nam pā lailāk : kō̜ranī sưksā ʻAmphœ̄ Mư̄ang Chaiyaphūm læ ʻAmphœ̄ Bān Khwao, Čhangwat Chaiyaphūm (Samnak Wičhai læ Khwāmrūammư̄ Rawāng Prathēt, Sūn Thēknōlōyī Sārasonthēt, Krom Pō̜ngkan læ Banthao Sāthārana Phai, 2010)
Application of remote sensing and Geographic Informaion System to monitor, analyze, and plan for landslide and sudden flood in Chiayaphum Province, Northeastern Thailand.